The Usage of Wood Materials in Architecture - Omonov Khusan Abdurazzakovich (Researchparks Publishing, 2022)
This article is dedicated to contemplate the usage of wood materials in the modern architecture. The purpose of this article is to introduce readers to a modern architecture, and show the place of wood in it. The article highlights the feature of applying the timber to the interior décor and how it will be advantageous in modern life. The main aspect of the research that formed the basis of this article are how the development of civilization and development of wood processing influences why timber is an acceptable option in the construction of houses and in the interior. Based on the researches of modern architect from wide web we may say that in the current constructions frequently observed the applying wood and modern types of timber. And according to this researches, the author put forward a number of proposals and recommendations aimed at introducing the readers to a modern constructions build of wood.